Правовий статус керівника місцевої прокуратури у кримінальному процесі - Назарук, О.; Nazaruk, О. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглядаються особливості правового статусу керівника місцевої прокуратури у кримінальному процесі. Визначено загальні положення керівництва в органах прокуратури. Розмежовано поняття керівництва та процесуального керівництва в органах прокуратури у сфері кримінального провадження. Окреслено основні аспекти реалізації повноважень керівника місцевої прокуратури у сфері кримінального провадження. Керівник місцевої прокуратури зобов’язаний вживати певні організаційні заходи безпосередньо для кримінального провадження, і хоча такі повноваження регламентуються нормами кримінального процесуального права, за своєю правовою природою вони є повноваженнями організаційно-управлінського характеру. Обгрунтовано необхідність внесення до чинного кримінального процесуального законодавства з питань діяльності керівника прокуратури у кримінальному провадженні. The article deals with the peculiarities of the legal status of the Head of the local prosecutor's office in the criminal proceedings. The legal status of the prosecutor is investigated as a multidimensional concept that includes general legal status of a person and a citizen, special legal status, and sectoral legal status that are regulated by the legislation of Ukraine. The head’s of the prosecution organizational and functional components have been singled out in the content of his legal status. The article determines common provisions of the management in the prosecution. The concepts of management and procedural guidance in the prosecution in criminal proceedingshave been demarcated. The author substantiated theidea that the Procedure supervisor oversees the observance of law in the form of procedural supervision, and that such management does not perform typical administrative activity, but its responsibility is, first of all, to ensure the proper fulfillment of criminal proceedings tasks. The head of the local prosecutor's officemust imply certain administrative arrangements directly to the criminal proceedings. Although these powers are regulated by the norms of criminal procedural law, they have the powers of organizational-managerial nature. The author lays emphasis on the necessity of amendments to the current criminal procedural legislation concerning the head’s of the prosecution activity and functions in criminal proceedings.
Legal Status of the Head of the Local Prosecutor’s Office in the Criminal Proceeding
Keywords: правовий статус; прокурор; керівник; місцева прокуратура; кримінальний процес; процесуальний керівник; кримінальне провадження; legal status; the prosecutor; the head; the local prosecutor; criminal proceedings; procedural supervisor; criminal proceeding